Gearing Up for a Vaccine Requirement: A Mixed Methods Study of COVID-19 Vaccine Confidence Among Workers at an Academic Medical Center. Issue 3 (May 2022) - Mahoney, Megan; Winget, Marcy; Brown-Johnson, Cati; de Borba, Lindsay; Veruttipong, Darlene; Luu, Jacklyn; Jones, David; Bohman, Bryan; Vilendrer, Stacie
SUMMARY: Goal: Assessing barriers to vaccination among healthcare workers may be particularly important given their roles in their respective communities. We conducted a mixed methods study to explore healthcare worker perspectives on receiving COVID-19 vaccines at a large multisite academic medical center. Methods: A total of 5, 917 employees completed the COVID-19 vaccine confidence survey (20% response rate). Most participants were vaccinated (93%). Compared to vaccinated participants, unvaccinated participants were younger (60% < 44 years), more likely to be from a non-Asian minority group (48%), and more likely to be nonclinical employees (57% vs. 46%). Among the unvaccinated respondents, 53% indicated they would be influenced by their healthcare provider, while 19% reported that nothing would influence them to get vaccinated. Key perceived barriers to vaccination from the qualitative analysis included the need for more long-term safety and efficacy data, a belief in the right to make an individual choice, mistrust, a desire for greater public health information, personal health concerns, circumstances such as prior COVID-19 infection, and access issues. Principal Findings: Strategies endorsed by some participants to address their concerns about safety and access included a communication campaign, personalized medicine approaches (e.g., individual appointments to discuss how the vaccine might interact with personal health conditions), and days off to recover. Mistrust and a belief in the right to make an individual choice may be harder barriers to overcome; further dialogue is needed. Applications to Practice: These findings reflect potential strategies for vaccine requirements that healthcare organizations can implement to enhance vaccine confidence. In addition, organizations can ask respected health professionals to serve as spokespeople, which may help shift the perspectives of unvaccinated healthcare workers.